A JPEG 2000 BASED HYBRID IMAGE COMPRESSION TECHNIQUE FOR MEDICAL IMAGES - Hussain, S. K.; Raja, G. (The Nucleus, 2011)
Use of lossy compression for medical images could result in compression error that may be considered as diagnostic problem by medical doctor. Hybrid schemes, a combination of lossy and lossless compression are used to achieve higher compression ratio without compromising the subjective quality of medical images. This paper proposes a new hybrid compression method for medical images. Different combinations of lossy and lossless compression schemes: RLE, LZW, JPEG LS, JPEG and JPEG2000 are implemented to find out the best hybrid compression combination by keeping subjective quality of medical image as a benchmark. X-ray images are used for experimentation. Experimental results show that hybrid combination of JPEG2000 lossless and lossy JPEG2000 produce optimized results without compromising subject quality of medical images required for diagnostics. The proposed hybrid combination has average compression ratio, space saving, MSE and PSNR of 0.21, 78.97, 1.16 and 47.58 respectively for all the medical images used in experimentation. The proposed hybrid scheme can be used for medical image compression.